A total smoking ban - an exploratory analysis of average monthly sick-leave use among public service employees before and after the introduction of a no-smoking policy - Fowler, Ken F., 1967- (1994)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1994. Psychology Bibliography: leaves 91-99 In a time-series design, sick-leave records of three- hundred and nine General Service employees from four Newfoundland government head offices were analyzed over a four-year period to determine if any change in average monthly sick-leave use resulted from the introduction of a no-smoking policy. Using three dependent measures, the total-time index (TTI), frequency index (Fl) and short-term index (STI), pre and post measures were assessed for possible changes through the use of ARIMA (p,d,q) procedures and ANOVA procedures where applicable. No significant change in absenteeism regardless of dependent measure, time of policy introduction, or department was found. Differences among dependent measures, the future of absenteeism research and the suitability of sick-leave use as an indicator of employee well-being are discussed.